New species and record of Pselaphinae (Coleoptera: Staphylinidae) from Saudi Arabia - Hlaváč, Peter; Sharaf, Mostafa R.; Aldawood, Abdulrahman S. (Zootaxa, 2013)
Centrophthalmus subtilissimus sp. nov. is described and the new record of Ctenistes staudingeri Schaufuss from Saudi Arabia is given. Both species were collected in the under rock ant nest of Pheidole cf. pallidula.